Wplyw klasy sportowey na zmiany stezenia kortyzolu we krwi u sprinterek po biegu na dystansie 100 m w czasie zawadow - Obminski, Z.; Lerczakl, K. (Sport wyczynowy, 2002)
Background. The aim of the study was to determine serum cortisol and blood lactate in two groups of female sprinters of the same age and athletic experience but differing in their sport class (more - A and less advanced), following 100 m competitions. Material and methods. The sprinters from the A group participated in the international Kusocinski Memorial, those from the L group - in a national competition. The competitions took place in the summer, in afternoon hours, on open stadiums, under windless conditions. Results. Men running times were 11.72 ± 0.11 and 12.29 ± 0.13 s in A and L groups, respectively. The pre- and post-running cortisol concentrations in Group A were 612 ± 151 and 1105 ± 282 nmol/L, respectively (p < 0.05). The post-running level in Group L increased only by 20%. Lactate concentrations were in both groups alike. Conclusions. It was concluded that more advanced sprinters reacted to competitive sprints with higher cortisol responses compared with their less experienced mates.